2024
DOI: 10.1007/s00401-024-02736-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide loss of heterozygosity predicts aggressive, treatment-refractory behavior in pituitary neuroendocrine tumors

Andrew L. Lin,
Vasilisa A. Rudneva,
Allison L. Richards
et al.

Abstract: Pituitary neuroendocrine tumors (PitNETs) exhibiting aggressive, treatment-refractory behavior are the rare subset that progress after surgery, conventional medical therapies, and an initial course of radiation and are characterized by unrelenting growth and/or metastatic dissemination. Two groups of patients with PitNETs were sequenced: a prospective group of patients (n = 66) who consented to sequencing prior to surgery and a retrospective group (n = 26) comprised of aggressive/higher risk PitNETs. A higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Therefore, germline genetic testing is only suggested in children. Regarding somatic testing, in aggressive macroadenomas, ATRX immunostaining could be informative, but genetic assessment of somatic DNA of the tumour is not recommended outside of clinical research settings in a recent publication, Lin et al identified TP53 variants or extensive LOH in 9/14 treatment-refractory corticotroph tumours, six of them carrying concomitant ATRX (four) or DAXX (two) alterations [309].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, germline genetic testing is only suggested in children. Regarding somatic testing, in aggressive macroadenomas, ATRX immunostaining could be informative, but genetic assessment of somatic DNA of the tumour is not recommended outside of clinical research settings in a recent publication, Lin et al identified TP53 variants or extensive LOH in 9/14 treatment-refractory corticotroph tumours, six of them carrying concomitant ATRX (four) or DAXX (two) alterations [309].…”
Section: Discussionmentioning
confidence: 99%